Comparison of iohexol with barium sulfate and Na-meglumine diatriozate in gastrointestinal radiography of dogs and cats - Kiliç, S; Canpolat, I (Scientific Technical Research Council Turkey, 2002)
In this study, 30% suspension of barium sulfate (BS) and 1/1 and 1/3 dilated solutions of Na-meglumine diatriozate (NMD) and iohexol (IO) were administered via the naso-gastric trackt to 3 dogs and 3 cats in two different doses, i.e. 5 ml/kg (lower dose) and 10 ml/kg (higher dose). Each application was repeated at 1-week intervals. Radiographs were taken prior to, and at certain intervals after, contract medium (CM) applications. According to the radiographs taken from the BS groups, CM was determined to be distributed unevenly in the stomach and to have a localized and segmented appearance in both the small and large intestines. In NMD groups, the radiographic (image) qualities of the stomach and large intestines were observed to be greater than those of the small intestine. The radiographic qualities of 10 groups were superior in all aspects to those of BS and NMD groups. When the data obtained from all CMs were evaluated together, the filling and emptying times of the stomach and the small and large intestines were found be significantly slower (P<0.05) in the BS group than in the NMD and 10 groups whilst having no difference (P>0.05) between the last two CMs. Regarding these parameters, there was no difference (P>0.05) between the various dilation rates of these CMs. Despite the statistically non-significant difference (P>0.05) the GIS transit times were longer in the higher doses of CMs than in the lower ones. Gastrointestinal system (GIS) transit speeds of CMs were found to be faster in cats than in dogs, When the results of all CMs used in this study were evaluated in total, it could be readily seen that each CM had different degrees of benefits as well as limitations. Therefore, it was suggested that prior to selecting a CM as a GIS contrast medium, the relationship between the complexity of the suspected pathological lesion and the potential benefits of one of these chosen CMs should be well established.
Köpek ve kedilerde gastrointestinal radyografide iohexol'un baryum sülfat ve Na-meglumin diatriozat ile karşilaştirilmasi
Keywords: iohexol; barium sulfate; Na-meglumine diatriozate; gastrointestinal radiography; cat; dog